2016
DOI: 10.1016/j.cell.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rates of Surface and Volume Synthesis Set Bacterial Cell Size

Abstract: Summary Many studies have focused on the mechanisms underlying length and width determination in rod-shaped bacteria. Here, we focus instead on cell surface area to volume ratio (SA/V), and demonstrate that SA/V homeostasis underlies size determination. We propose a model whereby the instantaneous rates of surface and volume synthesis both scale with volume. This model predicts that these relative rates dictate SA/V and that cells approach a new steady-state SA/V exponentially, with a decay constant equal to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
425
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(458 citation statements)
references
References 51 publications
28
425
4
1
Order By: Relevance
“…We used time-lapse imaging to measure cell size and cell cycle timing in SSB-GFP M. smegmatis cells. Several studies recently developed a division adder model (also called an incremental model) of cell size control, in which bacteria add a constant length (Δ l bd ) from birth to division regardless of birth size (Figures 2A, S2D&S4; STAR Methods) [6, 8, 2023]. Because Δ l bd is not correlated to birth length, we found that M. smegmatis is consistent with this aspect of the division adder model (Figure 2B) [4, 6, 19].…”
Section: Resultsmentioning
confidence: 99%
“…We used time-lapse imaging to measure cell size and cell cycle timing in SSB-GFP M. smegmatis cells. Several studies recently developed a division adder model (also called an incremental model) of cell size control, in which bacteria add a constant length (Δ l bd ) from birth to division regardless of birth size (Figures 2A, S2D&S4; STAR Methods) [6, 8, 2023]. Because Δ l bd is not correlated to birth length, we found that M. smegmatis is consistent with this aspect of the division adder model (Figure 2B) [4, 6, 19].…”
Section: Resultsmentioning
confidence: 99%
“…This scenario is referred to as the incremental or adder model. Recent work proposed a similar model, in which a constant surface area is added between birth and division (Harris and Theriot, 2016). Clearly, these models are different than Donachie’s – yet they both stem from empirical findings.…”
Section: Challenging Donachie’s Modelmentioning
confidence: 99%
“…Recent studies have investigated the mechanism of cell size control via inhibition of biosynthesis [4,10]. When cells were exposed to sub-lethal dosage of a cell wall biosynthesis inhibitor, their surface-to-volume ratio changed to a new steady-state value in a dose-dependent manner [10].…”
Section: Introductionmentioning
confidence: 99%